2020
DOI: 10.3390/ijerph17113751
|View full text |Cite
|
Sign up to set email alerts
|

Model for Taking Care of Patients with Early Childhood Caries during the SARS-Cov-2 Pandemic

Abstract: Pending the availability of vaccines to contain the SARS-CoV-2 pandemic, the current solution is “social distancing” with a reduction of dental treatments to those assessed as urgent and emergency cases. These treatments also involve Early Childhood Caries (ECC) due to the fact that this disease affects preschool children (a vulnerable population) and, in addition, shows a propensity to evolve into more serious complications (dental pain, infections). A narrative review was carried out to support a protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 64 publications
(73 reference statements)
1
38
0
6
Order By: Relevance
“…Thus, this fact has been revealed in meta-analyses that have investigated the effectiveness of these physical methods, as simple and low-cost interventions, to reduce respiratory virus infections [ 42 , 43 ]. Finally, our results confirmed that the risk of presenting the investigated clinical symptoms increases proportionally with age, the young ages being generally spared, as other authors stated [ 6 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, this fact has been revealed in meta-analyses that have investigated the effectiveness of these physical methods, as simple and low-cost interventions, to reduce respiratory virus infections [ 42 , 43 ]. Finally, our results confirmed that the risk of presenting the investigated clinical symptoms increases proportionally with age, the young ages being generally spared, as other authors stated [ 6 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Prevention and nonsurgical caries management include many options. Evidence-based materials include dental resin sealants, glass ionomers as sealants or as part of atraumatic restorative treatment performed with hand instruments, silver diamine fluoride, sodium fluoride varnish, and other self-applied and professionally applied topical fluorides (40)(41)(42). These materials can be applied without generating aerosols, reducing the risk of viral transmission.…”
Section: Going Forward: Opportunitiesmentioning
confidence: 99%
“…The prevention of dental caries through measures such as oral hygiene instructions, pit and fissure sealants, fluoride application, and diet analysis would be quite helpful in order to avoid or reduce the need for aerosol-generating restorative dental procedures in children. This could reduce the risk of viral infection transmission in the long term by reducing the need for advanced aerosol-generating dental procedures during the SARS-CoV-2 pandemic outbreak [34,35]. Moreover, the dental treatment procedures should be carried out under high standards of oral care and infection control, including patient examination prior to (telephone or telemedicine triage) or after attending a clinic (COVID19 questions form), clinical setting disinfection, medical wastes measures, reduction of the number of daily treated patients, and the use of personal protection during treatment [3,4,35].…”
Section: Discussionmentioning
confidence: 99%
“…This could reduce the risk of viral infection transmission in the long term by reducing the need for advanced aerosol-generating dental procedures during the SARS-CoV-2 pandemic outbreak [34,35]. Moreover, the dental treatment procedures should be carried out under high standards of oral care and infection control, including patient examination prior to (telephone or telemedicine triage) or after attending a clinic (COVID19 questions form), clinical setting disinfection, medical wastes measures, reduction of the number of daily treated patients, and the use of personal protection during treatment [3,4,35]. Furthermore, using high-volume suction, rubber dam, and four-handed dentistry techniques could help in reducing the viral disease spread during dental treatment [4,29,35,36].…”
Section: Discussionmentioning
confidence: 99%